The aesthetic unconscious - Rancière, Jacques (Polity, 2009)
This book is not concerned with the use of Freudian concepts for the interpretation of literary and artistic works. Rather, it is concerned with why this interpretation plays such an important role in demonstrating the contemporary relevance of psychoanalytic concepts. In order for Freud to use the Oedipus complex as a means for the interpretation of texts, it was necessary first of all for a particular notion of Oedipus, belonging to the Romantic reinvention of Greek antiquity, to have produced a certain idea of the power of the thought that does not think, and the power of the speech that remains silent. From this it does not follow that the Freudian unconscious was already prefigured by the aesthetic unconscious. Freud's "aesthetic" analyses reveal instead a tension between the two forms of unconscious. --From publisher's description.